VARIABEL-VARIABEL PENENTU STRUKTUR MODAL PERUSAHAAN NON KEUANGAN DI BURSA EFEK INDONESIA - Krisna Dewi, Putu Ayu Govika; Wiksuana, I Gusti Bagus; Rahyuda, Henny (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan, 2017)
Purpose of study is to analyze variables that determine capital structure of non-financial companies in Indonesia. There are seven variables observed namely company's growth rate, profitability, firm size, asset structure, liquidity, non-debt tax shield and business risk. The population were non-financial companies listed on Indonesia Stock Exchange during 2010-2014 and published annual financial statements in 2009-2014. Study used census technique. Population consisted of 324 companies. Data analysis technique used was multiple regression model for panel data. The results show that profitability, firm size and non-debt tax shield (NDTS) had significant effect on capital structure. Study concluded that profitability and non-debt tax shield are determinant variables of capital structure on non-financial firms in Indonesia based on trade-off theory approach while firm size tends to follow other capital structure theory.
Keywords: variabel penentu struktur modal, trade-off theory